Early Cognitive Development and Its Effect on Learning Outcomes in Statistics Education - Rahmawati, Rahmawati (Journal La Edusci, 2024)
This study explores the impact of initial abilities on learning outcomes in the Education Statistics course at STIT DDI Pasangkayu. Using a descriptive and quantitative approach, data from 22 students were analyzed. Correlation and simple linear regression analyses, performed with SPSS software, revealed a strong positive correlation (r = 0.754) between students' initial abilities and their final exam scores. The coefficient of determination (r² = 0.568) indicates that initial abilities account for approximately 56.8% of the variance in learning outcomes. The significance of this relationship (p = 0.022) underscores the crucial role of early cognitive skills in academic success. Although initial abilities are a significant predictor of performance, 43.2% of the variance is influenced by other factors, highlighting the need for a broader approach that includes additional variables to fully understand academic achievement. These findings emphasize the importance of assessing students' initial abilities and considering other contributing factors to enhance learning outcomes.